Perioperative Health Education Improves Coping Mechanisms in Preoperative Cataract Patients - Enggal Hadi Kurniyawan; Popi Dyah Putri Kartika; Siswoyo; Wantiyah; Murtaqib; Fitrio Deviantony; Yeni Fitria (Health and Technology Journal (HTechJ), 2023)
Patients with cataracts can experience psychological and physiological impacts; the physiological impact caused is discomfort in sight, while the psychological impact on patients is anxiety because they will have surgery on the eye. This study aims to analyze the effect of providing perioperative health education on the coping mechanisms of preoperative cataract patients. This study used a quasi-experimental research design with a pre-test and post-test research approach with a control group design. The research sampling technique used is consecutive. The sample in this study were cataract patients who were going to perform cataract surgery as many as 30 respondents. Analysis of the data used using the dependent t-test and independent t-test. This study's results indicate differences in coping mechanisms in the measurement of the treatment and control groups, with a p-value = 0.001. This study concluded that there were significant differences in coping mechanisms after being given perioperative health education in the treatment group and the control group. Nurses are expected to be able to apply health education to preoperative cataract patients so that the patient's coping becomes adaptive and ready for surgery